TECHNIQUE OF DESIGNING OF TECHNOLOGICAL PROCESSES OF CENTRIFUGAL PROCESSING - Yu.A. PROSKORJAKOVA (Advanced Engineering Research, 2009)
Article is devoted to research of process of centrifugal processing. Theoretical models are developed for definition of an average arithmetic deviation of a structure of the established roughness, depth of the strengthened layer and a degree of hardening. The technique of designing of technological processes of centrifugal processing is offered.